ISOINDOLINOTRIAZOLE DERIVATIVES: SYNTHESIS BY THE AZIDE-ALKYNE CYCLOADDITION CLICK CHEMISTRY (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A novel series of isoindolinotriazole derivatives with different substituents in the triazole moiety were synthesized via copper-catalyzed cycloaddition (CuAAC) click chemistry between 2-(meta- or para-ethynylphenyl)-4,6-dimethoxyisoindolin-1-ones and several azides. The synthesized triazoles were characterized by IR, 1H NMR, 13C NMR and mass spectral techniques.